2008
DOI: 10.1161/strokeaha.107.492348
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intraarterial and Intravenous Thrombolysis for Ischemic Stroke With Hyperdense Middle Cerebral Artery Sign

Abstract: Background and Purpose-It is unclear whether intraarterial (IAT) or intravenous (IVT) thrombolysis is more effective for ischemic stroke with hyperdense middle cerebral artery sign (HMCAS) on computed tomography (CT). The aim of this study was to compare IAT and IVT in stroke patients with HMCAS. Methods-Comparison of data from 2 stroke units with similar management of stroke associated with HMCAS, except that 1 unit performed IAT with urokinase and the other IVT with plasminogen activator. Time to treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(123 citation statements)
references
References 30 publications
3
112
1
5
Order By: Relevance
“…Further small randomized clinical trials of prourokinase (PROACT I) 29 and urokinase (MELT) 30 and a meta-analysis of the PROACT I, PROACT II, and MELT trials suggest that intra-arterial thrombolysis can be beneficial in patients with proximal MCA occlusion. Although intra-arterial thrombolysis with rt-PA is not supported by randomized clinical trials, data from observational and nonrandomized comparative studies suggest it can be beneficial 31,32 . A nonrandomized trial compared patients with and without hyperdensity of the MCA territory at baseline CT who were then given intravenous or intra-arterial rt-PA. Intravenous rt-PA therapy was associated with less favorable outcomes in patients with hyperdense MCA sign as compared to patients without it 33 .…”
Section: Protocol For Intra-arterial Thrombolysismentioning
confidence: 99%
“…Further small randomized clinical trials of prourokinase (PROACT I) 29 and urokinase (MELT) 30 and a meta-analysis of the PROACT I, PROACT II, and MELT trials suggest that intra-arterial thrombolysis can be beneficial in patients with proximal MCA occlusion. Although intra-arterial thrombolysis with rt-PA is not supported by randomized clinical trials, data from observational and nonrandomized comparative studies suggest it can be beneficial 31,32 . A nonrandomized trial compared patients with and without hyperdensity of the MCA territory at baseline CT who were then given intravenous or intra-arterial rt-PA. Intravenous rt-PA therapy was associated with less favorable outcomes in patients with hyperdense MCA sign as compared to patients without it 33 .…”
Section: Protocol For Intra-arterial Thrombolysismentioning
confidence: 99%
“…For these patients, IAT may be considered as an alternative to IV thrombolysis, although currently IV tPA is the only validated approach and its use is recommended to a maximum of 4.5 h from stroke onset [10]. In 1 observational study of 112 patients with a hyperdense middle cerebral artery sign (MCA), in which half the patients received IVand the other half received IAT, a favorable outcome was doubled and the risk of death was reduced by 2/3 in patients treated with IAT [15]. However, such provocative studies merely emphasize the need for a randomized trial comparing IV therapy with endovascular therapy.…”
Section: Indicationsmentioning
confidence: 99%
“…A total of 177 patients were enrolled in the Multi MERCI trial, but the device was deployed in only 164 patients, with a mean age of 68.1± 16.0 years. The median NIHSS score was 19 (range, [15][16][17][18][19][20][21][22][23], and the median procedural duration was 1.6 h (1.2-2.3 h). As in the MERCI trial, the patients had a high thrombus burden with ICA terminus occlusion (32%), M1 or M2 segments of the MCA branch occlusion (60%), and posterior circulation occlusion (8%).…”
Section: Mechanical Clot Disruption and Extractionmentioning
confidence: 99%
“…Previous studies of acute MCA occlusions reported a favorable clinical outcome at 3 months in 41% and 63% of patients by using a combined IV-endovascular strategy, 10,11 in 56% by using combined IV-IA thrombolysis, 6 and in 40% and 53% by using IA thrombolysis alone. 4,5 Comparatively, patients included in our IES group presented with high rates of favorable outcome at 3 months (77%). This was also the case in patients who underwent only mechanical thrombectomy (67%).…”
Section: Discussionmentioning
confidence: 92%
“…2,3 Given the strong correlation between prompt recanalization and favorable clinical outcome, more invasive approaches such as IA thrombolysis, bridging IV-IA rescue strategy, and combined IV-IA thrombolysis have been recommended (recanalization rates ranging from 45% to 71%). [4][5][6][7][8] In cases of persistent proximal artery occlusion following IV or IA thrombolysis, additional mechanical thrombectomy was proposed with promising results in terms of recanalization (87%) compared with IVT alone (52%). Clinical outcome tended to be better at 3 months following thrombectomy (mRS Յ2 in 57% of patients) but without reaching statistical significance (P ϭ .35).…”
mentioning
confidence: 99%